If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -4 = -1b + 12 Reorder the terms: -4 + 3b = -1b + 12 Reorder the terms: -4 + 3b = 12 + -1b Solving -4 + 3b = 12 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. -4 + 3b + b = 12 + -1b + b Combine like terms: 3b + b = 4b -4 + 4b = 12 + -1b + b Combine like terms: -1b + b = 0 -4 + 4b = 12 + 0 -4 + 4b = 12 Add '4' to each side of the equation. -4 + 4 + 4b = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 4b = 12 + 4 4b = 12 + 4 Combine like terms: 12 + 4 = 16 4b = 16 Divide each side by '4'. b = 4 Simplifying b = 4
| 0=t-3 | | w+3=15 | | 9+m=6 | | 10=n+1 | | -12=w-5 | | 4=n+6 | | 19=w+7 | | -7+w=-13 | | 11=w+2 | | 1=k+6 | | b+10=13 | | -2=m-7 | | (5x^2-6x+8)(3x+3)=0 | | a/-7=-7 | | b/6=-4 | | a/2=-2 | | -3w=-21 | | w-7=-1 | | (x^5+x^3+x)(x^2-1)=0 | | -7+t=-5 | | b+9=20 | | 4+k=5 | | -12=a-9 | | 6+t=13 | | -7+a=-11 | | (3x^2+6x+9)(8x-4)=0 | | a+7=19 | | -5d=-5 | | d+10=21 | | 4d=4 | | t/7=-4 | | 4x-1=8x+29 |